2016
DOI: 10.1007/s11010-016-2756-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced P-selectin expression on platelet-a marker of platelet activation, in young patients with angiographically proven coronary artery disease

Abstract: P-selectin (CD62p) exposure is an established marker for platelet activation. P-selectin exposure can trigger variety of thrombotic and inflammatory reactions. In patients with coronary artery disease (CAD), platelets are activated, and hence, there is increased P-selectin exposure. The role of P-selectin exposure in patients on treatment with statins and anti-platelets is conflicting. A case-control study was performed to determine P-selectin exposure in consecutively recruited 142 patients (age ≤ 55 years) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…P-selectin, on the other hand, was another known marker of platelet procoagulant activity that exposed on the platelet membrane when the platelet was activated (39). Besides, P-selectin can mediate the adhesion of activated platelet with other cells, leading to the hypercoagulant state of the blood (40). More recently, Prakash et al found that P-selectin can even promote thrombus propagation independently of both von Willebrand factor and thrombospondin-1 in mice (41).…”
Section: Discussionmentioning
confidence: 99%
“…P-selectin, on the other hand, was another known marker of platelet procoagulant activity that exposed on the platelet membrane when the platelet was activated (39). Besides, P-selectin can mediate the adhesion of activated platelet with other cells, leading to the hypercoagulant state of the blood (40). More recently, Prakash et al found that P-selectin can even promote thrombus propagation independently of both von Willebrand factor and thrombospondin-1 in mice (41).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CD62P exposure is known to be an established marker for platelet activation. Current research has found that the percentage expression of CD62P on platelets without any stimulation by platelet-activating factors, such as ADP, collagen, and thrombin, is higher in CAD patients compared to participants in a control group [3]. Tenaglia et al [4] also reported significantly greater CD62P staining on atherectomy specimens from patients with unstable angina than from patients with stable angina.…”
Section: Introductionmentioning
confidence: 98%
“…This process is usually considered to be a compensatory response of the heart to an increased hemodynamic load, which could cause contractile depression, ventricular dilatation, interstitial cardiac fibrosis, and eventually heart failure (HF) (Ooi et al, 2015). Studies have shown that platelet activation played a critical role in several cardiovascular diseases, such as HF (Schafer et al, 2003), coronary artery disease (George et al, 2016), and atrial fibrillation (Lim et al, 2014). Platelet activation is followed by platelet adhesion that is characterized by expression of variety of glycoproteins on platelet surface.…”
Section: Introductionmentioning
confidence: 99%